The total amount of CRP within the first 72 h after STEMI is crucial for the outcome. (14th October 2021) - Garlichs, C; Ries, W; Torzewski, J; Pfluecke, C D; Darius, H; Heigl, F; Ince, H; Mitzner, S; Nordbeck, P; Butter, C; Sheriff, A; ,
Abstract: Background: The CAMI-1 study dealt with the depletion of CRP by apheresis in patients with acute myocardial infarction (AMI). CRP, the prototype human acute phase protein, has been known as a marker of poor prognosis in AMI and independently predicts 30-day mortality. Methods: 66 STEMI patients were enrolled following complete coronary revascularization (2–12 h after AMI). 32 patients received CRP apheresis, whereas 34 patients treated by standard protocols served as controls. CRP apheresis started 24±12 h and 48±12 h after onset of symptoms. A specific CRP adsorber removed ≤79% of the original CRP. 6000 ml of plasma was treated via peripheral venous access. Primary endpoint was myocardial infarction size as determined by Cardiac Magnetic Resonance Imaging (CMR) 3–9 days after STEMI. Results: Aphereses sessions were well tolerated with no relevant side effects. The expected peak CRP level after AMI can be calculated precisely with 2–3 CRP quantifications during the first 24h after the onset of symptoms (CRP gradient). The regression coefficient for this analysis is 0.91. This mathematical step allows for the comparison of the CRP-apheresis group and the controls on the basis of their individual CRP gradients. The mean CRP gradient does not differ between both groups, whereas the mean area under the curve (AUC) of CRP within the first 72 h after AMI does. Thus, there was no bias in CRP kinetics between the two groups. The AUC of CRP is a significant indicator for infarct size (p=0.002), LVEF (p<0.001), circumferential strain (p<0.001), longitudinal strain (p=0.021). Therefore, the aphereses patients performed significantly better at all endpoints than the controls. The CRP apheresis significantly reduced myocardial damage by a reduction of the AUC of CRP. To our surprise, two apheresis patients had an infarct size of 0%. Conclusions: For the first time we find an unequivocal association between myocardial infarct size and the AUC of CRP. The results show a significant beneficial effect of CRP apheresis on myocardial infarction size and wall motion. Selective CRP apheresis is now being further evaluated as a therapeutic approach in the treatment of acute myocardial infarction in a registry (CAMI registry). FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Pentracor GmbH